Being disconnected from life: meanings of existential loneliness as narrated by frail older people. (3rd October 2018) - Sjöberg, Marina; Beck, Ingela; Rasmussen, Birgit H; Edberg, Anna-Karin
ABSTRACT: Objectives: This study illuminated the meanings of existential loneliness (EL) as narrated by frail older people. Method: Data were collected through individual narrative interviews with 23 people 76–101 years old receiving long-term care and services. A phenomenological hermeneutical analysis was performed, including a naïve reading and two structural analyses as a basis for a comprehensive understanding of EL. Result: Four themes were identified related to meanings of EL: (1) being trapped in a frail and deteriorating body; (2) being met with indifference; (3) having nobody to share life with; and (4) lacking purpose and meaning. These intertwined themes were synthesized into a comprehensive understanding of EL as 'being disconnected from life'. Conclusion: Illness and physical limitation affects access to the world. When being met with indifference and being unable to share one's thoughts and experiences of life with others, a sense of worthlessness is reinforced, triggering an experience of meaninglessness and EL, i.e. disconnection from life. It is urgent to develop support strategies that can be used by health care professionals to address older people in vulnerable situations, thereby facilitating connectedness.